A Modified Body Force Model for a Submerged Waterjet - Dakui Feng; Yongyan Ma; Zichao Cai; Pengwei Yang; Yanlin Zou (Journal of Marine Science and Engineering, 2025)
The submerged waterjet exhibits advantages such as uniform inflow, minimal flow distortion, and excellent acoustic performance, making it particularly suitable for high-speed vessels. This study investigates the open-water characteristics of the submerged waterjet and develops a body force model for the submerged waterjet propulsion system. First, under uniform inflow conditions, numerical simulations were performed using the body force method by replacing the rotor with a virtual blade and simultaneously replacing both the rotor and stator. The results of the body force model were then compared in detail with those obtained using the sliding mesh method. Second, the influence of the inflow velocity plane position on the results of the body force model was analyzed. The results indicate that the body force method, which replaces both the rotor and stator with a virtual blade, fails to accurately simulate the forces acting on various components of the propeller and the true distribution of the propeller’s flow field. In contrast, the method that replaces only the rotor with a virtual blade produces results for component forces and flow fields that are largely consistent with the results of the sliding mesh method, demonstrating the stability and reliability of the body force model. Additionally, the position of the inflow velocity plane has no significant effect on the model’s computational results.